PENGARUH MEDIA SOSIAL, HEDONIC SHOPPING MOTIVATION, DAN TEMAN SEBAYA TERHADAP IMPLUSE BUYING PADA MAHASISWA UKI TORAJA - Lilia Bulqsha Toding; Mey E.Limbongan; Mince Batara (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to measure the extent of the influence of social media, hedonic shopping motivation, and peer influence on impulse buying among students of the Management Study Program, Faculty of Economics, UKI Toraja. The method used is a quantitative approach through the distribution of questionnaires to 94 respondents. The data were analyzed using validity test, reliability test, classical assumption test, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that hedonic shopping motivation, and peer influence have a positive and significant effect on impulse buying, while social media does not have a significant effect on impulse buying This is indicated by the t-table value of 1.661 with a significance level of 0.000 < 0.05, and the F-value of 33.760 which is greater than the F-table (3.10) with a significance level of 0.000 < 0.05. These findings confirm that the ease of obtaining information through social media, the pleasure-driven motivation in shopping, and peer influence can increase students’ tendency to engage in impulse buying. The R² value of 0.529 indicates that social media, hedonic shopping motivation, and peer influence contribute 52.9% to changes in impulse buying. Thus, these variables are proven to be effective in influencing impulse buying behavior among students of the Management Study Program, Faculty of Economics, UKI Toraja.